Imagem 3D de biomicroscopia ultrassônica do gastrocnêmio lateral de rato em processo de reparação após lesão por laceração - D’Agostini, Juliana Geremia (2017)
This Dissertation had the objective to generate tridimensional (3D) ultrasonic biomicroscopic (UBM) images, obtained from a sequence of 2D images acquired from the rat right lateral gastrocnemius (LG) muscle, and the following-up of the lesion volume after the lesion laceration process. UBM, an ultrasound 2D image generation technique using frequencies higher than 20 MHz, provides image spatial resolutions compatible with small animal dimensions. Wistar rats, distributed into groups control (n=3), sham (n=3) and with the right LG partially lacerated (n=4) were used. For those animals in groups sham and with LG lesion, a sequence of 20 MHZ UBM-2D images were acquired immediately before and after, 3, 7, 14, 21 and 28 days after surgical procedure. The animals in control group had their images acquired at a 7 days interval and during 28 days. The images were processed to highlight the important structures of the GL on the UBM-3D images and to mark the legion region. After processing the images, the sequences were used to reconstruct, based on texture technique, the 3DUBM images of the right LG muscle, with the lesion volume visualized. The 3D-UBM images demonstrated efficiency in the following-up of the muscle repairing process. The lesion volume presented a tendency to decrease to 50% of the lesion volume measured seven days after surgery.